1998
DOI: 10.1097/00004872-199816110-00010
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate as marker of sympathetic activity

Abstract: These data suggest that the supine heart rate can be regarded as a marker of intersubject differences in sympathetic tone, and that this is the case both in the general population and in those with cardiovascular diseases. Its value for this purpose is limited, however, and the limitations may be more evident in essential hypertension than in conditions such as obesity and heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
170
3
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(186 citation statements)
references
References 17 publications
9
170
3
4
Order By: Relevance
“…However, the precise nature of the pathophysiological relationship underlying the increased risk of hyperglycaemia in those with an elevated heart rate has not been explained. Resting heart rate is a marker of the autonomic nervous system, with elevated heart rate reflecting a shift in autonomic balance toward enhanced sympathetic nervous activity and reduced vagal tone (21). Some evidence suggests that sympathetic activation contributes to the development of insulin resistance in humans (7,8,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise nature of the pathophysiological relationship underlying the increased risk of hyperglycaemia in those with an elevated heart rate has not been explained. Resting heart rate is a marker of the autonomic nervous system, with elevated heart rate reflecting a shift in autonomic balance toward enhanced sympathetic nervous activity and reduced vagal tone (21). Some evidence suggests that sympathetic activation contributes to the development of insulin resistance in humans (7,8,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…RHR is an indicator of sympathetic activity (12) and an increased sympathetic nerve system induces both acute and chronic insulin resistance (9, 10, 11). The major organs involved in insulin Table 2 The risk of RHR per 10 bpm on incident T2DM in patients with clinically manifest vascular diseases, after stratification in three age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chronically increased sympathetic nerve activity can precede the development of insulin resistance and obesity (10,11). RHR reflects sympathetic tone, and correlates with muscle sympathetic nerve activity and noradrenaline serum levels (12). An increased RHR identifies subjects at higher risk for developing cardiovascular disease and mortality (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with hypertension, MSNA has been reported to be higher than [5][6][7] or similar to 8 -10 measurements in normotensive control subjects. Studies in normal subjects have reported that MSNA is linked to heart rate (HR) 11 but is unrelated to blood pressure. 12,13 The link between HR and blood pressure is more compelling.…”
mentioning
confidence: 99%